YEVGENIY FYODOROVICH LEVITSKY (TO THE 70th BIRTHDAY) - статья Редакционная (Бюллетень сибирской медицины)
The creative biography of the famous Russian scientist – Honored Scientist of Russia, MD, Director (1990 to 2011), chief scientific officer of the Tomsk Research Institute of Balneology and Physiotherapy FMBA of Russia, Head (1995 to 2012) of Chair of Rehabilitation Medicine, Physiotherapy and Health Resort of Siberian State Medical University (Tomsk), Professor Ye.F. Levitsky is presented. The main trends of scientific and social activities of the scientist are concerned.